Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/cncr.28375
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phenotype of the foci in multifocal invasive breast carcinomas: Intertumoral heterogeneity is related to shorter survival and may influence the choice of therapy

Abstract: BACKGROUND Multiple synchronous, ipsilateral, invasive foci of breast carcinomas are frequent and are associated with a poorer prognosis. Few studies have investigated the prognostic and therapeutic implications of heterogeneity of such foci. METHODS The authors reviewed the tumor type, grade, and size of all invasive foci in a series of 110 multifocal breast carcinomas documented on large‐format slides. Molecular phenotype was determined by immunohistochemistry in tissue microarray blocks using 3 classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
7
29
0
Order By: Relevance
“…Molecular characterization of each cancer focus to distinguish between MC and MF cancers may be important in future classifications8. Intertumoral heterogeneity in MIBC has been reported in 11–27 per cent of patients8 13, 14. Generally, evaluation of the largest cancer using standard immunohistochemical (IHC) biomarkers (oestrogen and progesterone receptors, human epidermal growth factor receptor 2 (HER2) and Ki‐67) is performed3 9, 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular characterization of each cancer focus to distinguish between MC and MF cancers may be important in future classifications8. Intertumoral heterogeneity in MIBC has been reported in 11–27 per cent of patients8 13, 14. Generally, evaluation of the largest cancer using standard immunohistochemical (IHC) biomarkers (oestrogen and progesterone receptors, human epidermal growth factor receptor 2 (HER2) and Ki‐67) is performed3 9, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, evaluation of the largest cancer using standard immunohistochemical (IHC) biomarkers (oestrogen and progesterone receptors, human epidermal growth factor receptor 2 (HER2) and Ki‐67) is performed3 9, 15. However in future, the potential to use extended IHC biomarkers and whole‐genome sequencing may increase the recognition of intertumoral heterogeneity14 16, 17, 18, with prognostic implications19, 20, 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…We and other authors have demonstrated that multiple breast carcinomas can differ among foci regarding histology and molecular profile (28,49,53). No studies however analyzing the impact of this heterogeneity on axillary metastases have been performed in multiple breast carcinomas.…”
Section: Molecular Profilementioning
confidence: 95%
“…There is a positive correlation between the presence of axillary lymph node metastases and the number of tumour foci [4,5]. In multiple carcinomas, between 3% and 37.5% of cases may have different histological tumour types and/or histological grades (inter-tumour heterogeneity) [3,[6][7][8][9][10]. This is related to shorter survival and may influence the choice of therapy [6].…”
Section: Introductionmentioning
confidence: 99%
“…In multiple carcinomas, between 3% and 37.5% of cases may have different histological tumour types and/or histological grades (inter-tumour heterogeneity) [3,[6][7][8][9][10]. This is related to shorter survival and may influence the choice of therapy [6]. There are older studies published in English literature concerning the impact of the morphological/ immunohistochemical features of unifocal/multiple tumour foci on the morphological/immunohistochemical features of lymph node metastases [11,12].…”
Section: Introductionmentioning
confidence: 99%